Approach to emerging challenges for Community Social Work from the experience of Covid-19. Towards a participatory design of social policies - Eito-Mateo, Antonio; García-Martínez, Jesús; Matías-Solanilla, Antonio (Acciones e Investigaciones Sociales, 2021)
This article attempts to reflect on the importance that Com- munity Social Work (CSW) can have in aiding the co-production of public policies. The goal is to highlight, from a community and participatory point of view, the need for greater involvement of users of the social services sys- tem in the design of those policies that most affect them. The methodology used is of an exploratory nature, involving significant documentary review. Although our results are not conclusive, they do point to the need to pro- gressively involve all actors in the dynamics of new social policy designs, especially given the impact of Covid-19 on social service structures. It con- cludes by highlighting the need to activate new roles for CSR professionals to encourage the social empowerment processes of the beneficiaries of such policies.